KUALITAS ES KRIM VITA TRADISIONAL - Thresia Dewi Kartini Berek; Mustamin Mustamin; Hijrah Asikin; Fitrahyani Ahmad; Asrini Agus (Media Gizi Pangan, 2023)
Handling nutritional problems in toddlers is one of them by providing additional food, such as snacks, biscuits and ice cream. Ice cream as a processed food product can add energy and there is more value because it has functional properties with the substitution of cowpea (Vigna unguiculata) in vita ice cream. The purpose of the study was to determine the acceptability, protein content, fat, and physical properties of vita ice cream. The research design was one shot study case with 4 formulas namely F0 (standard formula), F1, F2 and F3. The results showed that the most favourable vita ice cream was F2 vita ice cream. The cowpea substitution in vita ice cream does not affect the overrun of ice cream and the higher the cowpea substitution, the longer the melting time of vita ice cream. The higher the cowpea substitution, the higher the protein content in vita ice cream with an average value of 4.38 g (F3). Conversely, the higher the cowpea substitution, the lower the fat content of vita ice cream, which is in the range with an average value of 11.57 g (F0) to 9.22 g (F3). The conclusion of this study is that vita ice cream F2 is acceptable from the aspects of colour, aroma, texture and taste with protein content of 3.81 g/100g and fat content of 9.55 g/100g of vita ice cream.